2015
DOI: 10.1371/journal.pone.0125763
|View full text |Cite
|
Sign up to set email alerts
|

New Short Tandem Repeat-Based Molecular Typing Method for Pneumocystis jirovecii Reveals Intrahospital Transmission between Patients from Different Wards

Abstract: Pneumocystis pneumonia is a severe opportunistic infection in immunocompromised patients caused by the unusual fungus Pneumocystis jirovecii. Transmission is airborne, with both immunocompromised and immunocompetent individuals acting as a reservoir for the fungus. Numerous reports of outbreaks in renal transplant units demonstrate the need for valid genotyping methods to detect transmission of a given genotype. Here, we developed a short tandem repeat (STR)-based molecular typing method for P. jirovecii. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 56 publications
3
57
1
Order By: Relevance
“…Regarding the ability to determine mixtures of P. jirovecii genotypes in samples, STR typing studies reported 70% (Parobek) and 68% (Gits-Muselli) of genotype mixtures, which was confirmed with a European study that analyzed 249 samples (68% of mixtures) [22,23,87]. The maximal ratio of mixture detection using simulated mixed samples was 1/50 [22].…”
Section: Short Tandem Repeat (Str)supporting
confidence: 57%
See 3 more Smart Citations
“…Regarding the ability to determine mixtures of P. jirovecii genotypes in samples, STR typing studies reported 70% (Parobek) and 68% (Gits-Muselli) of genotype mixtures, which was confirmed with a European study that analyzed 249 samples (68% of mixtures) [22,23,87]. The maximal ratio of mixture detection using simulated mixed samples was 1/50 [22].…”
Section: Short Tandem Repeat (Str)supporting
confidence: 57%
“…The selected methods should also be capable of detecting mixtures, and in particular, have the ability to detect minority alleles. Detection of mixtures is an important aspect in the study of P. jirovecii transmission and epidemiology, considering that up to 92% of patients' respiratory samples present coinfections [17,[21][22][23][24][25].…”
Section: Genotyping Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, there is only one report on this topic, which concerned P. jirovecii genotypes in French Guiana (Le Gal et al, 2015) located 7,000 km from metropolitan France whereas there are no data on genomic characteristics of P. jirovecii from Réunion, located 9,300 km from metropolitan France and 12,000 km from French Guiana (Figure 1). Conversely, numerous data on P. jirovecii genotypes are available for metropolitan France (Nevez et al, 2003;Totet et al, 2003;Le Gal et al, 2013;Maitte et al, 2013;Gits-Muselli et al, 2015;Alanio et al, 2016;Desoubeaux et al, 2016;Charpentier et al, 2017;Vindrios et al, 2017). In this context, the main objective of the present study was to identify P. jirovecii multilocus genotypes in patients living in Réunion and to compare these genotypes with those identified using the same method in patients living in metropolitan France or French Guiana.…”
Section: Introductionmentioning
confidence: 98%